Double‐shelled hollow mesoporous silica incorporated copper (II) (Cu/DS‐HMS‐NH2) as a catalyst to promote in‐situ esterification/transesterification of low‐quality palm oil. (18th July 2021) - Rahadi, Antonius Nova; Martinus, Jeremia Jonathan; Santoso, Shella Permatasari; Yuliana, Maria; Kurniawan, Alfin; Gunarto, Chintya; Hartono, Sandy Budi; Soetaredjo, Felycia Edi; Ismadji, Suryadi
Summary: To encourage the utilization of low‐quality palm oil with high free fatty acid and moisture content (>0.1 wt%), a novel catalyst with two spatial shells and different active sites, double‐shelled hollow mesoporous silica incorporated copper (II) (Cu/DS‐HMS‐NH2 ), is fabricated via the two‐stage hydrolysis and condensation technique. The influence of four parameters (eg, catalyst loading, temperature, reaction time, and the mass ratio of methanol to degummed palm oil (DPO)) on the yield of fatty acid methyl ester (FAME) are monitored and optimized using a combination of response surface methodology (RSM) and face centered‐central composite experimental design (CCF‐CCD). The optimized FAME yield is predicted at 86.63 wt% and experimentally obtained at 87.14 ± 0.11 wt% (FAME purity of 98.45 ± 0.67 wt%) under the following optimum condition: 55.3°C, 5 h, methanol to DPO mass ratio of 5.3:1, and 5 wt% catalyst loading. The experimental and predicted values are proportional and in direct agreement with an error of 0.51%. The goodness of fit analysis also indicates conformity between the mathematical model and the experimental results. The reusability study shows that Cu/DS‐HMS‐NH2 is stable until the fifth run, evident from the yield of FAME which stays above 80%. These results prove the potential utility of Cu/DS‐HMS‐NH2 for the direct conversion of low‐quality vegetable oils to biodiesel without any pre‐treatment. Abstract : Cu/DS‐HMS‐NH2 is successfully fabricated to convert low‐quality palm oil to biodiesel (FAME) in a one‐pot synthesis. The textural properties of Cu/DS‐HMS‐NH2 are comparable to the existing heterogeneous catalyst, with SBET of 733.24 m 2 g −1, and Vp of 0.54 cm 3 g −1 . The maximum FAME yield at 87.14 ± 0.11 wt% with the purity of 98.45 ± 0.67 wt% was obtained using Cu/DS‐HMS‐NH2 at 55.3°C, 5 h, methanol to DPO mass ratio of 5.3:1, and 5 wt% catalyst loading, indicating its high catalytic activity.